Applicability of the Dual-Factor Model of Mental Health in the Mental Health Screening of Chinese College Students - Xiao, Rong; Zhang, Chao; Lai, Qiaozhen; Hou, Yanfei; Zhang, Xiaoyuan (Frontiers in Psychology, 2021)
Traditional mental health models focus on psychopathological symptoms. In contrast, a dual-factor model of mental health integrates psychopathology and subjective well-being into a mental health continuum, and it is adjustment and supplement for traditional mental health research paradigm. The present study explores the applicability of a dual-factor model of mental health in mental health screening of Chinese college students. To assess mental health statues of 2065 college students, we used Flourishing Scale Chinese Version, Satisfaction with Life Scale, the seven item Patient Health Questionnaire, the Mental Health Continuum Short Form and Purpose in Life Test-Short Form. Results showed that the dual-factor model of mental health has a good fit index. Also, a feasible screening scale was addressed. The results indicate the importance of addressing both subjective well-being and psychopathology in evaluating mental health screening of college students.